A Mixed Methods Approach to Assessing Roaming Reference Services - Askew, Consuella (Evidence Based Library and Information Practice, 2015)
Abstract Objective – The objectives of this research are threefold: a) to assess the students’ perception of the roaming service at the point of service; b) to assess the librarians’ perception of the service; and, c) to solicit librarian feedback and observations on their roaming experience and perceived user reactions. Ultimately, this data was used to inform and identify best practices for the improvement of the roaming service. Methods – A combination of quantitative and qualitative survey methodologies were used to collect data regarding patron and librarian service perceptions. Patrons and librarians were asked to complete a survey at the conclusion of each reference transaction. In addition at the end of the first semester of the implementation, librarians were asked to provide feedback on the overall program by responding to five open-ended questions. Results – The findings indicate that our students typically seek assistance from the librarians once a term (58%), but the majority (71%) indicated that they would seek a librarian’s assistance more frequently, if one were available on the various floors of the library. Overall, our users indicated that they were “Satisfied” (36%) to “Very Satisfied” (43%) with the roaming service. Librarian responses indicate overall enthusiasm and positive feelings about the program, but cautioned that additional enhancements are needed to ensure the continued development and effectiveness of the service. Conclusion – Overall, patrons were satisfied with the service delivered by the roaming reference librarian. The roaming librarians also provided positive feedback regarding the delivery of service. Data collected from both groups is also in agreement on two major program aspects needing improvement: marketing of the service and a means by which to easily identify the roaming librarian.